Strategi Marketing Sebagai Upaya Meningkatkan Penjualan Produk Di Hdi Family Center Kraksaan Probolinggo Dalam Perspektif Syariah - Fajri, Ahmad; Qomariyah, Qomariyah; Armanto, Nuruddin (universitas Islam Zainul Hasan Genggong, 2023)
In the current era, the marketing strategy has become a benchmark in developing the business world. Market conditions that are increasingly expanding can encourage entrepreneurs to implement their marketing strategies properly. By implementing a good and targeted marketing strategy, this can attract consumers to buy products. The purpose of this study is to determine marketing strategies in increasing sales of HDI Family Center Kraksaan products from a sharia perspective. At this writing the method used is descriptive qualitative, besides that in collecting data used is from secondary data sourced from publications which include scientific journals, books, websites, which are sourced from interviews. The end result of this writing is to show that marketing strategies can be applied to increase sales using the mix marketing method. In addition, there is also targeting and segmenting which are important references in marketing strategies.